Criminal pre-trial proceedings in the Republic of Kazakhstan: Trend of the institutional transformations - Akhpanov, A.; Sabitov, S.; Shaykhadenov, R. (Opción, 2018)
Crime Prevention is one the basic policies in social control area. Although total experience in different policy zones of social crimes management is providing, and several theorists in the field provide theories, but in the Republic of Kazakhstan, yet the lack of a comprehensive policy in this area is felt more than ever. In this paper, it has been tried to examine the weaknesses and ambiguities of this crime prevention investigation using the documentary and library study method.